To compare the efficacy and safety of intralesional kenacort injection vs surgical intervention (Incision and Curettage) in primary Chalazion - Lohana, ND Pagarani (Pakistan Journal of Ophthalmology, 2021)
ABSTRACT PURPOSE To compare the efficacy and safety of intralesional steroid injection versus surgical intervention (Incision and Curettage) in Primary Chalazion. STUDY DESIGN A six months prospective, comparative and interventional hospital based study. PLACE AND DURATION OF STUDY Study was done at Shaheed Mohtarma Benazir Bhutto Medical College Lyari and Sindh Government Lyari General Hospital, Karachi. Duration of study was six months from 15th October, 2016 to 15th April, 2017. MATERAILS AND METHODS This was a Prospective, Comparative, Interventional study with the use of probability sampling technique. The Study was conducted at Shaheed Mohtarma Benazir Bhutto Medical College Lyari and Sindh Government Lyari General Hospital, Karachi for duration of six months from 15th October, 2016 to 15th April, 2017. 50 eyes of 50 patients between the age group of 15 to 40 years and of either gender diagnosed with chalazion on clinical basis from the Out patients department of Ophthalmology of Shaheed Mohtarma Benazir Bhutto Medical College Lyari were included in the study. All patients were randomly divided into two groups with 25 patients in each group. Group 1 received intralesional 0.2 ml triamcinolone acetonide while Group 2 received surgical intervention (Incision and Curettage). RESULTS In a total of 50 patients the mean age was 25±12.2 with male to female ratio of 2:1. 19 (76%) patients achieved complete resolution of chalazion after intra lesional triamcinolone acetonide in group I and 21 (84%) patients out of 25 achieved complete resolution of chalazion after incision and curettage in group II. No ocular complication such as bleeding, elevation of intra ocular pressure, eye lid de-pigmentation or any loss of vision in either group was observed. CONCLUSION Intra lesional triamcinolone acetonide injection is equally effective as incision and curettage in primary chalazion. It means it is a good alternative first line treatment in cases where diagnosis is straight forward. KEYWORDS Intra Lesional Triamcinolone Acetonide, Surgical Intervention